1995
DOI: 10.1111/j.1399-3011.1995.tb00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐function relationships of des‐(B26‐B30)‐insulin

Abstract: In order to study the role of the amino acid in position B25 and its environment in shortened insulins, a series of analogues was prepared with the following modifications; 1, Stepwise shortening of the B‐chain including replacements of TyrB26 and ThrB27 by glycine; 2, substitutions at the carboxamide nitrogen of des‐(B26‐B30)‐insulin‐B25‐amide by apolar, polar or charged residues of various chain lengths; 3, replacement of PheB25 by asparagine‐amide, phenylalaninol or a series of alkyl and aralkyl residues. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Unexpectedly, alanine was found to be nearly equivalent to native hormone 142 while asparagine exhibited still higher activity. 157 Crystal structures of DPI and related analogs have been reported. 158,159 They demonstrate conservation of the structural elements central to receptor recognition, with one notable difference.…”
Section: Insulin Structure and Function 701mentioning
confidence: 98%
“…Unexpectedly, alanine was found to be nearly equivalent to native hormone 142 while asparagine exhibited still higher activity. 157 Crystal structures of DPI and related analogs have been reported. 158,159 They demonstrate conservation of the structural elements central to receptor recognition, with one notable difference.…”
Section: Insulin Structure and Function 701mentioning
confidence: 98%
“…DTI-NH 2 was shown to have 110% binding affinity and 129% in vitro biological activity . Likewise, DPI-NH 2 , which is equipotent to insulin at binding (100−115%) ,,, , retained full in vivo hypoglycemic activity after intravenous injection into rats . These data and the results relating to analogues with specific substitutions at the B26 position do not support the hypothesis that residues B26−B30 are important for biological activity, and instead, we suggest that the observed discrepancy between binding affinity and biological activity of the shortened analogues could be caused by N-methylation of the B25−B26 peptide bond and specific substitutions at the B26 position.…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies have shown that deleting the last five highly conserved residues at the C-terminus of the insulin B-chain still results in a molecule with significant potency. 77,78,91 In fact, changes in the new C-terminus (B25) of these truncated molecules, provide variants with increased potency at the IR compared to WT-Ins. 77,78,92 These insulins of different length and C-terminal modifications provided an ideal opportunity to explore the generalizability of MD/FEP as an in silico mutagenesis tool in peptide design.…”
Section: Discussionmentioning
confidence: 99%